Analysis of Student Conceptions and Conceptional Changes about Chemical Equilibrium Materials in Concentration Factors - Dian Novita; Suyono Suyono; Suyatno Suyatno (IJORER : International Journal of Recent Educational Research, 2023)
Objective: This study aims to determine the conception and changes in the conception of the concentration factor in chemical equilibrium material. Method: The method used in this study is a mixed method, which is a combination of qualitative and quantitative methods, namely the Concurrent Embedded Strategy, which is a combination of qualitative methods and quantitative methods carried out at the same time. Results: The test instruments provided can reduce the misconceptions that exist in students when viewed from a comparison of the number of students who experience misconceptions from 13.33% in the first stage to 7.00% in the last stage. Students understand enough about chemical equilibrium shifts but still need clarification, especially in writing down changes in reaction equations when chemical equilibrium is disturbed and analyzing phenomena using metacognitive examples of a concept in their surroundings. Novelty: This research reveals that students' misconceptions can be reduced using worksheets with five processing stages. This novelty can provide (1) solutions related to identifying students' misconceptions and (2) reducing students' misconceptions regarding chemical equilibrium concentration factors.